2015
DOI: 10.1037/a0039021
|View full text |Cite
|
Sign up to set email alerts
|

Initial abstinence status and contingency management treatment outcomes: Does race matter?

Abstract: Objective Limited research has evaluated African American substance users’ response to evidence-based treatments. This study examined the efficacy of contingency management (CM) in African American and White cocaine users. Method A secondary analysis evaluated effects of race, treatment condition, and baseline cocaine urine sample results on treatment outcomes of African American (n = 444) and White (n = 403) cocaine abusers participating in one of six randomized clinical trials comparing CM to standard care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 67 publications
1
7
1
Order By: Relevance
“…In contrast to multiple studies pointing to poorer substance use outcomes among African Americans (Field et al, 2012; Montgomery et al, 2011; Montgomery, Carroll, & Petry, 2015), findings from the current analysis suggest comparable retention and efficacy of the behavioral and pharmacological treatments evaluated in these trials for African American and White cocaine users. This is a significant finding given the use of data from five carefully controlled RCTs examining the effectiveness of contingency management, cognitive behavioral therapy, twelve-step facilitation, interpersonal therapy, and disulfiram.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In contrast to multiple studies pointing to poorer substance use outcomes among African Americans (Field et al, 2012; Montgomery et al, 2011; Montgomery, Carroll, & Petry, 2015), findings from the current analysis suggest comparable retention and efficacy of the behavioral and pharmacological treatments evaluated in these trials for African American and White cocaine users. This is a significant finding given the use of data from five carefully controlled RCTs examining the effectiveness of contingency management, cognitive behavioral therapy, twelve-step facilitation, interpersonal therapy, and disulfiram.…”
Section: Discussioncontrasting
confidence: 94%
“…Interventions that are tailored to older adults and severe cocaine users for African American and White adults, respectively, might result in improved treatment outcomes. Second, given that other studies have found racial differences in outcomes (Field et al, 2012; Montgomery et al, 2011, 2015), more research is needed to identify factors (e.g., socioeconomic status; Saloner & Cook, 2013) that might contribute to the inconsistent findings. Third, the inconsistent findings on racial health disparities in cocaine use outcomes suggest that additional studies are needed to disentangle the effects of race in treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…White participants had higher placebo response rates than racial minority participants, possibly reflecting previously observed racial differences in response to CM (Montgomery et al, 2012, 2015). Racial minority participants’ poorer response to CM may have allowed NAC effects to emerge, as suggested by a two-fold NAC versus placebo difference in abstinence outcomes.…”
Section: Discussionmentioning
confidence: 58%
“…Not all evidence-based practices perform equally as well across subgroups. For example, treatment outcomes were not as favorable for African American cocaine users as they were for Caucasian cocaine users in a contingency management trial (Montgomery, Carroll, & Petry, 2015). We should note that any treatment outcome analyses using “race categories” as an independent variable are relatively rare.…”
Section: Discussionmentioning
confidence: 99%